2015
DOI: 10.1063/1.4934932
|View full text |Cite
|
Sign up to set email alerts
|

Marangoni boundary layer flow and heat transfer of copper-water nanofluid over a porous medium disk

Abstract: In this paper we present a study of the Marangoni boundary layer flow and heat transfer of copper-water nanofluid over a porous medium disk. It is assumed that the base fluid water and the nanoparticles copper are in thermal equilibrium and that no slippage occurs between them. The governing partial differential equations are transformed into a set of ordinary differential equations by generalized Kármán transformation. The corresponding nonlinear two-point boundary value problem is solved by the Homotopy anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 40 publications
(73 reference statements)
1
23
0
Order By: Relevance
“…Hamid and Arifin (2014) extended both problems (Arifin et al 2013;Sastry et al 2013) by applying the wall mass suction and injection while Mat et al (2013) imposed a thermal radiation parameter. Lin and Zheng (2015) observed the flow of copper-water nanofluid over a porous medium disk. Ellahi et al (2016) and Lin et al (2016) explored the particle shape effects on the Marangoni convection flow whereas Sheikholeslami and Ganji (2017) and Sheikholeslami and Chamkha (2017) examined the influence of Lorentz force.…”
Section: Introductionmentioning
confidence: 99%
“…Hamid and Arifin (2014) extended both problems (Arifin et al 2013;Sastry et al 2013) by applying the wall mass suction and injection while Mat et al (2013) imposed a thermal radiation parameter. Lin and Zheng (2015) observed the flow of copper-water nanofluid over a porous medium disk. Ellahi et al (2016) and Lin et al (2016) explored the particle shape effects on the Marangoni convection flow whereas Sheikholeslami and Ganji (2017) and Sheikholeslami and Chamkha (2017) examined the influence of Lorentz force.…”
Section: Introductionmentioning
confidence: 99%
“…Thus second grade fluid has been dealt with the linearized form of thermal radiation. Homotopy analysis method [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] has been implemented for the development of convergent series solution for velocity, temperature and nanoparticle concentration. Graphical results for velocity, temperature and nanoparticle concentration are analyzed for various embedded parameters of interest.…”
mentioning
confidence: 99%
“…The base fluid, water, is packed with SWCNTs and MWCNTs. Further, the governing equations for the flow form may be expressed as (1)(2)(3)(4)(5):…”
Section: Mathematical Scheme Of the Problemmentioning
confidence: 99%
“…The first contribution to this research area was by Napolitano [2] during his survey of steady dissipative layers. Lin and Zheng [3] theoretically investigated the problem of Marangoni boundary layer flow and heat transfer of copper-water nanofluid over a porous medium disk. They concluded that the Marangoni parameter has a destabilizing effect on all the other parameters such as temperature, shear stress, velocity, and boundary layer velocity.…”
Section: Introductionmentioning
confidence: 99%